Human Rights and the East African Crude Oil Pipeline in Kabale Subcounty, Hoima District, Uganda - Calvin Amanya (Uganda Christian University, 2023)
This thesis examines the effects of oil industry on the people of Kabaale Sub County, Hoima, and Bunyoro region in Uganda. The thesis analyses the current political Economy of Uganda and how Uganda is prepared to utilize the proceeds from the oil Industry for the development of the country and its people. In addition, the research examines the effects of industry on the people of Uganda by analyzing how the people Of Kabaale in Bunyoro region were affected by the plans to construct oil refinery in their Region. This field research was done using qualitative methods and the Historical Materialism theoretical framework guided the study. The major findings include; Displacement of people from land especially women, lack of accountability from the Leadership, and less citizen participation in the policy formulation and oil industry. Ugandans, East Africans and the wider Pan-African world need to re-organize their Socio-economic structure to enable people own means of production; participate and Form labor organizations. Additionally, there is a need for oil producing African countries To unite and setup and oil fund for resources and investment instead of relying on Foreign multinationals or become rentier states.
This is a dissertation.